The nucleotide sequence at the 3'-end of Neurospora crassa 25S-rRNA and the location of a 5.8S-rRNA binding site. - Kelly, J M (1981)
The sequence of 110 nucleotides adjacent to the 3'-end of Neurospora crassa 25S-rRNA has been derived by chemical sequencing methods. Sequences present between 40 and 85 nucleotides of the 3'-end were found to complement sequences at the 3'- and 5'-ends of 5.8S-rRNA. Interaction was shown to occur between 5.8S-rRNA and a specific 3'-terminal fragment of 85 nucleotides derived from 25S-rRNA. We have also demonstrated that the nucleotide sequence at the 3'-end of N. crassa 5.8S-rRNA (-UCAUUOH) is different from the published sequence (-UUUUOH) which was derived from rDNA.